INTEGRATION OF TECHNOLOGIES IN MODERN PEDAGOGY (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article examines the issues of technology integration in modern pedagogy. Modern pedagogy faces many challenges and problems that require careful analysis and the search for effective solutions. In a rapidly changing world, where technologies and social conditions are constantly evolving, educational systems must adapt to new realities.